Effect of e-book media on adolescent girls’ knowledge of mental health issues anxiety - Nofita Tudang Rombeallo; Indrawati Aris Tyarini; Ari Setiawati (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Adolescence is a critical developmental stage marked by psychological, emotional, and social changes. Anxiety is among the most common mental health issues faced by adolescents and can significantly affect their academic achievement, social relationships, and overall well-being. This study aimed to examine the effect of e-book media on the knowledge level of adolescent girls regarding mental health issues, specifically anxiety. Methods: This research employed a pre-experimental design with a one-group pretest–posttest approach. The population consisted of adolescent girls enrolled at Madrasah Aliyah Muhammadiyah Salaka, with 62 respondents selected through total sampling. Data collection used a structured questionnaire measuring knowledge about anxiety-related mental health issues. Statistical analysis was conducted using the Wilcoxon Signed Rank Test through SPSS version 29.0 to compare pretest and posttest scores. Results: The findings revealed a significant improvement in knowledge after the intervention. Before using e-book media, 54.8% of respondents had low knowledge, 40.3% moderate knowledge, and only 4.8% high knowledge. Following the intervention, 74.2% demonstrated high knowledge and 25.8% moderate knowledge, with no respondents remaining in the low knowledge category. Statistical analysis indicated a p-value of 0.000 (<0.05), confirming a significant effect of e-book media in enhancing knowledge. Conclusion: E-book media is proven to be an effective educational tool for increasing adolescent girls’ knowledge about mental health, particularly anxiety. Its accessibility and interactive format make it a valuable medium for promoting adolescent mental health literacy in school settings. Future studies are recommended to expand to larger populations and integrate other digital learning resources.